PENGEMBANGAN APLIKASI CMS BERBASIS MOBILE SEBAGAI KEUNGGULAN DISTINGSI PROGRAM STUDI ILMU AL-QUR’AN DAN TAFSIR - Muhammad Maimun; Nurul Bahiyah; Iid Muhyidin; M. Fathur Ramadhan S.; Saluky Saluky (UIN Siber Syekh Nurjati Cirebon, 2024)
The ability of a study program to develop its uniqueness is a significant advantage. This uniqueness is a distinctive characteristic that sets it apart from study programs at other universities or campuses. In this context, the Al-Qur’an and Tafsir Studies Program at UIN Siber Syekh Nurjati Cirebon has a unique focus on information and computer technology. To realize this distinctiveness, this research aims to develop an Android-based CMS application. The application is designed to host the works of the academic community within the study program, including both scientific and non-scientific works. The data collection methods used include direct observation and literature review. The method used to develop the application is the SDLC (System Development Life Cycle) method, which involves stages such as Analysis, Design, Implementation, Testing, Deployment, and Maintenance. The software utilized includes PHP and MySQL. The research resulted in the creation of the